Broad Escovopsis-inhibition activity of Pseudonocardia associated with Trachymyrmex ants - Meirelles, Lucas A. [UNESP]; Mendes, Thais D.; Solomon, Scott E.; Bueno, Odair C. [UNESP]; Pagnocca, Fernando C. [UNESP]; Rodrigues, Andre [UNESP] (Wiley-Blackwell, 2014)
Attine ants maintain an association with antibiotic-producing Actinobacteria found on their integuments. Evidence supports these bacteria as auxiliary symbionts that help ants to defend the fungus gardens against pathogens. Using Pseudonocardia strains isolated from Trachymyrmex ants, we tested whether the inhibitory capabilities of such strains are restricted to Escovopsis parasites that infect gardens of this ant genus. Twelve Pseudonocardia strains were tested in in vitro bioassays against Escovopsis strains derived from fungus gardens of Trachymyrmex (n = 1) and leaf-cutting ants (n = 3). Overall, significant differences were observed in the mycelial growth among each Escovopsis strain in the presence of Pseudonocardia. Particularly, Escovopsis from Acromyrmex and Trachymyrmex were the most inhibited strains in comparison to Escovopsis isolated from Atta. This result suggests that Pseudonocardia isolated from Trachymyrmex possibly secrete antimicrobial compounds effective against diverse Escovopsis strains. The fact that Trachymyrmex ants harbour Pseudonocardia strains with broad spectrum of activity and its defensive role on attine gardens are discussed.